Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1023/b:nere.0000018836.82122.23
|View full text |Cite
|
Sign up to set email alerts
|

Dihydropiridines Mechanism of Action in Striatal Isolated Nerve Endings: Comparison with ω-Agatoxin IVA

Abstract: The relative contribution of Ca2+ and Na+ channels to the mechanism underlying the action of the dihydropiridines (DHPs), nimodipine, nitrendipine and nifedipine was investigated in rat striatum synaptosomes. The rise in internal Ca2+ (Ca(i), as determined with fura-2) induced by high K+ was unchanged by the DHPs, which like tetrodotoxin (TTX) inhibited both the rise in internal Na+ (Na(i), as determined with the Na+ selective indicator dye, SBFI) and the rise in Ca(i) induced by veratridine. Nimodipine and ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
14
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 44 publications
3
14
0
Order By: Relevance
“…We studied if voltage-sensitive calcium channels participate in this gambierol-induced calcium entry. For this purpose we incubated the fura-2 loaded neuroblastoma cells with nitrendipine (a L and N-type calcium channel blocker) [46][47][48], and found a significant inhibition in cytosolic calcium increment induced by the toxin. We postulate that voltage-sensitive calcium channels play an important role in this cytosolic calcium increment.…”
Section: Discussionmentioning
confidence: 99%
“…We studied if voltage-sensitive calcium channels participate in this gambierol-induced calcium entry. For this purpose we incubated the fura-2 loaded neuroblastoma cells with nitrendipine (a L and N-type calcium channel blocker) [46][47][48], and found a significant inhibition in cytosolic calcium increment induced by the toxin. We postulate that voltage-sensitive calcium channels play an important role in this cytosolic calcium increment.…”
Section: Discussionmentioning
confidence: 99%
“…These methods were based on techniques including HPLC [9][10][11][12], GC-MS [4,13], CE-MS [14], CE/laser induced fluorescence detection [15], electrochemical sensor [16], spectrophotometry [17]. and HPLC-MS [18].…”
Section: Introductionmentioning
confidence: 99%
“…The role of voltage sensitive sodium channels in the mode of action of 4-aminopyridine, first suggested by the sensitivity of the Ca 2+ response induced by 4-aminopyridine to the Na + channel blocker, tetrodotoxin (Tibbs et al, 1989;Heemskerk et al, 1991) was later demonstrated in cerebral isolated nerve endings using the Na + selective indicator dye, SBFI (Galván & Sitges 2004). The involvement of K + channels in the mode of action of 4-aminopyridine at the presynaptic brain level, first suggested by the changes on 86 Rb + fluxes in brain nerve endings (Sitges et al, 1986), was confirmed later using the K + selective indicator dye, PBFI (Galindo & Sitges 2004). In summary, in cerebral isolated nerve endings 4-aminopyridine increases Na + channels permeability (Galván and Sitges, 2004), Ca 2+ channels permeability (Tibbs et al, 1989;Heemskerk et al, 1991;Galván & Sitges, 2004;, and decreases K + channels permeability (Sitges et al, 1986;Galván & Sitges, 2004).…”
mentioning
confidence: 76%
“…Neurotransmitter release evoked by veratridine in synaptosomes isolated from the whole brain or different brain regions is also highly sensitive to the blockade of Na + channels with tetrodotoxin and absolutely dependent on the presence of external Na + , but is independent of external Ca 2+ (Sitges, 1989;Sitges & Chiu, 1995a;Galindo & Sitges, 2004;Sitges & Galindo, 2005). This Ca 2+ independence of veratridine induced responses is particularly valuable as it allows testing the inhibitory effect of compounds on responses selectively mediated by activation of presynaptic voltage sensitive sodium channels in the cerebral isolated nerve endings.…”
Section: Introductionmentioning
confidence: 99%